Preparation method of oil shale ash-based zeolite material capable of efficiently adsorbing heavy metal cadmium

By melting activation and crystallization in the alkali fusion and hydrothermal process of oil shale ash slag and alkali, an oil shale ash-based zeolite material that efficiently adsorbs heavy metal cadmium is directly prepared, which solves the problems of process complexity and environmental pollution in the existing technology, and achieves an efficient and economical adsorption effect of heavy metal cadmium.

CN119841324APending Publication Date: 2025-04-18CANGZHOU NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510078189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when using oil shale ash slag to prepare zeolite materials, acid solutions need to be pretreated or additional silicon-containing or aluminum-containing chemicals are added, which increases process complexity and production costs and creates new environmental pollution problems. At the same time, the adsorption effect of the prepared zeolite material on heavy metal cadmium has not been verified.

Method used

Through a simple alkali fusion and hydrothermal process, the oil shale ash slag is directly mixed with the alkali, melt activation and low-temperature aging, and finally crystallized at an appropriate temperature to prepare an oil shale ash-based zeolite material that efficiently adsorbs heavy metal cadmium.

Benefits of technology

This method simplifies the process flow, reduces production costs, and avoids environmental pollution caused by acid treatment and the addition of additional chemicals. The prepared zeolite material has high crystallinity, large specific surface area and suitable pore size, showing excellent adsorption effect of heavy metal cadmium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841324A_ABST
    Figure CN119841324A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an oil shale ash-based zeolite material capable of efficiently adsorbing heavy metal cadmium, and aims to solve the problems of oil shale ash pollution and cadmium-containing wastewater treatment. According to the technical scheme, the method comprises the following steps: by taking oil shale or ash obtained by burning oil shale semicoke as an initial raw material, firstly carrying out pre-treatment operations such as drying, crushing and screening, then mixing with alkali, uniformly grinding, carrying out the steps of high-temperature melting activation, cooling and screening, adding water, stirring and aging, constant-temperature crystallization and the like, and finally, carrying out solid-liquid separation, washing, drying, crushing and screening, thereby obtaining the high-purity oil shale. The zeolite adsorption material is successfully prepared. The material is used for adsorbing heavy metal cadmium in wastewater and shows a remarkable effect. The method has the outstanding advantages that raw materials are not required to be pretreated by an acid solution, silicon-containing or aluminum-containing chemical substances are not required to be additionally added, the process is simple and environment-friendly, the cost is low, efficient utilization of solid wastes and effective treatment of cadmium-containing wastewater are realized, the method has important environment-friendly and economic values, and a new technical thought and method are provided for related fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource utilization and inorganic functional material preparation, and in particular to a method for preparing an oil shale ash-based zeolite material capable of efficiently absorbing heavy metal cadmium. Background Art

[0002] Oil shale is a sedimentary rock in which inorganic minerals and organic kerogen coexist. The content of inorganic minerals is very high, usually between 50% and 90%. At present, the main ways to utilize oil shale are pyrolysis to refine shale oil and direct combustion to generate electricity. These utilization processes will produce a large amount of solid waste - oil shale ash. Oil shale ash is mainly piled up in the open air, which not only occupies land resources, but also causes significant pollution to the environment such as water and soil due to the trace heavy metals in it. It has become an important factor restricting the further development of the oil shale industry.

[0003] The main components of oil shale ash are silicon dioxide and aluminum oxide, which are similar to the chemical composition of natural zeolite precursors. Therefore, the preparation of zeolite using oil shale ash as raw material can not only effectively reduce the cost of raw materials, but also provide a new direction for the resource utilization of this solid waste, thereby achieving green and high value-added development. At the same time, with the rapid development of non-ferrous metal smelting, electroplating and other industries, the discharge of a large amount of cadmium-containing wastewater has caused serious environmental problems. Cadmium ions are highly toxic, highly cumulative and difficult to degrade, posing a great threat to the ecosystem and human health. Therefore, the use of oil shale ash to prepare zeolite adsorption materials and use them to treat wastewater containing heavy metal cadmium has the dual advantages of "using waste to treat pollution".

[0004] The Chinese patent with application publication number CN101723397A discloses "a method for preparing zeolite molecular sieves from oil shale waste residue", in which the raw material oil shale ash residue needs to be treated with sulfuric acid before it can be used for the preparation of zeolite molecular sieves; the Chinese patent with application publication number CN119100384A discloses "a method for synthesizing activated carbon analcite from oil shale residue", in which the oil shale ash residue needs to be pretreated with hydrochloric acid before zeolite can be prepared; the Chinese patent with application publication number CN110357122B discloses "a method for synthesizing X-type zeolite by modifying oil shale residue", in which the raw material oil shale ash residue needs to be treated with hydrochloric acid, and aluminum hydroxide powder needs to be added additionally, only in this way can X-type zeolite be prepared. Obviously, these operations not only increase the complexity and production cost of the process flow of preparing zeolite using oil shale ash residue, but also generate new waste liquid, bringing additional environmental pressure. In addition, whether the zeolite adsorbent material prepared by these methods can be used as an effective treatment agent for heavy metal cadmium wastewater has not been explained.

[0005] Therefore, using solid waste oil shale ash as raw material, a method is developed to develop a method that does not require the use of acid solution to pretreat the raw materials and does not require the addition of additional silicon- or aluminum-containing chemicals. The method can directly prepare zeolite materials with high heavy metal cadmium adsorption performance through a simple alkali melting hydrothermal process. This method has important environmental value, economic value and practical application significance. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing an oil shale ash-based zeolite material, which does not require the use of an acid solution to pretreat the oil shale ash, nor does it require the addition of additional silicon- or aluminum-containing chemicals to the raw materials. The zeolite adsorption material is prepared using only a simple alkali melting hydrothermal process, and the prepared zeolite material has excellent adsorption performance for heavy metal cadmium.

[0007] The method for preparing an oil shale ash-based zeolite material for efficiently adsorbing heavy metal cadmium of the present invention comprises the following steps:

[0008] 1. The first is the raw material pretreatment stage. Oil shale ash is a key raw material, which comes from the combustion of oil shale or oil shale semi-coke. It needs to be dried, and the drying temperature is appropriately controlled at 80-120°C, which helps to remove moisture from the raw material so that it can better participate in the subsequent reaction. Then the raw material is crushed to reduce the particle size, and then screened through a 60-200 mesh sieve to ensure that the raw material has a uniform particle size and meets the requirements of the subsequent reaction, laying the foundation for the subsequent steps;

[0009] 2. Enter the mixing stage of oil shale ash and alkali. The alkali can be selected from sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, sodium carbonate, etc. The pretreated oil shale ash and alkali are mixed at a mass ratio of 1:0.5-1:2.5. To ensure that the two are fully and evenly mixed, grinding can be performed with the help of a mortar or mechanical stirring equipment to make the alkali and oil shale ash fully contact and promote the subsequent reaction;

[0010] 3. The subsequent melt activation step is crucial. Place the evenly mixed sample in a muffle furnace or other suitable high-temperature heating equipment and melt-activate it at a high temperature of 300-900°C for 0.5-4 hours. During this process, the high temperature causes a series of chemical reactions in the raw materials, changing their structure and properties. After the melt is cooled, grind and sieve again, and the mesh size of the sieve is also 60-200 to obtain a uniform activated product to ensure the consistency and stability of subsequent reactions;

[0011] 4. Then comes the low-temperature aging process, where the sieved melt is mixed with deionized water at a mass ratio of 1:1-1:8, and stirred and aged for 0.5-4 hours at a temperature of 10-40°C. At this stage, the reaction system is further stabilized and homogenized under relatively mild conditions to form an aged product, preparing for the subsequent crystallization process;

[0012] 5. In the crystallization step, the aged product is transferred to a suitable reaction vessel and reacted and crystallized at a constant temperature of 60-120°C for 4-48 hours. During this period, the zeolite crystal structure gradually grows and improves, and finally forms a crystallized product with good adsorption performance;

[0013] 6. Finally, the post-processing stage of the crystallized product is to separate the solid and liquid in the crystallized product by solid-liquid separation methods such as centrifugal separation, filtration or static precipitation. The separated solid is repeatedly washed with deionized water until the washing liquid is neutral to remove the impurity ions that may remain. Then it is placed in an oven at 105-110°C to dry to constant weight, and then crushed and sieved with a sieve mesh of 60-200 mesh to obtain the final oil shale ash-based zeolite adsorption material.

[0014] An application of an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium, specifically:

[0015] The zeolite adsorption material prepared by the present invention is used to treat wastewater containing heavy metal cadmium. The cadmium ion concentration of the treated wastewater ranges from 50 to 600 mg / L, the pH value of the wastewater is maintained between 3 and 9, the adsorption temperature is controlled at 10 to 60° C., and the adsorption time is 1 to 240 minutes. During the adsorption process, in order to ensure that the zeolite adsorption material is in full contact with the wastewater, stirring or oscillation can be used to make the adsorption process more efficient. At the same time, considering that there may be large particle impurities in the wastewater that will affect the adsorption effect, the wastewater needs to be initially filtered before adsorption to remove these impurities and ensure the smooth progress of the adsorption process.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. Cost and environmental advantages: Solid waste oil shale ash is directly used as raw material, and there is no need to pre-treat the raw material with acid solution, nor to add additional silicon- or aluminum-containing chemicals. This greatly simplifies the process flow, reduces production costs, and avoids the generation of new waste liquid caused by acid treatment and the addition of additional chemicals, effectively reducing environmental pollution, realizing the resource utilization of solid waste, and has important environmental and economic benefits.

[0018] 2. Excellent material performance: The prepared zeolite adsorption material has high crystallinity, large specific surface area, and good matching between pore size and cadmium ion radius. It performed outstandingly in the adsorption experiment, and its adsorption effect on cadmium ions in wastewater was significantly better than that of clay, other zeolites, unmodified biochar and other adsorbents. It has shown strong application potential in the treatment of heavy metal cadmium wastewater, and provides an efficient and low-cost adsorbent for the treatment of heavy metal ion wastewater.

[0019] 3. Industry promotion effect: The present invention opens up a new way for the efficient utilization of oil shale ash, and also provides a new means for the development of heavy metal wastewater treatment technology. It is of great significance to promote the sustainable development of related industries and promote the coordinated progress of solid waste resource utilization and environmental protection industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the process of preparing the zeolite adsorption material of the present invention and adsorbing heavy metal cadmium;

[0021] Figure 2 is the XRD pattern of the zeolite adsorbent material prepared in Example 1 of the present invention;

[0022] Figure 3 is a SEM image of the zeolite adsorption material prepared in Example 1 of the present invention;

[0023] Figure 4 is the adsorption-desorption curve of the zeolite adsorption material prepared in Example 1 of the present invention;

[0024] Figure 5 is a SEM image of the zeolite adsorption material prepared in Example 2 of the present invention;

[0025] Figure 6 is the XRD pattern of the zeolite adsorbent material prepared in Example 2 of the present invention;

[0026] Figure 7 is the adsorption-desorption curve of the zeolite adsorption material prepared in Example 2 of the present invention;

[0027] Figure 8 is the XRD pattern of the zeolite adsorbent material prepared in Example 3 of the present invention;

[0028] Fig. 9 This is a SEM image of the zeolite adsorbent material prepared in Example 3 of the present invention.

[0029] Fig.10 This is the adsorption-desorption curve of the zeolite adsorption material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and examples. The reagents involved in the examples can be purchased through conventional market channels unless otherwise specified; the experimental methods and operations involved are carried out in accordance with conventional operating specifications unless otherwise specified. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0031] like Figures 1 to 10 As shown,

[0032] Example 1

[0033] 1. Raw material pretreatment: The ash from the combustion of oil shale in the Balikun area of ​​Xinjiang is selected as the raw material. It is placed in an oven at 110°C for drying. The drying time is determined according to the water content of the ash and the performance of the drying equipment, generally 2-4 hours, to ensure that the water in the ash is fully evaporated. After drying, it is crushed into fine particles using a pulverizer. During the crushing process, it is necessary to pay attention to controlling the crushing time and speed to avoid excessive crushing that causes particle agglomeration or produces too much fine powder that affects subsequent screening. Then use a 100-mesh sieve for screening operations, and obtain the Balikun oil shale ash raw materials below 100 mesh by screening. The sieve can be vibrated appropriately during screening to ensure the screening effect.

[0034] 2. Alkali mixing process: The above-obtained oil shale ash raw material is mixed with sodium hydroxide in a mass ratio of 1:1.3. When mixing, the two are placed in a mortar and initially stirred to make the two preliminarily mixed evenly, and then the grinding intensity and frequency are gradually increased, and the grinding is continued for 15-20 minutes to ensure that the sodium hydroxide can be evenly dispersed in the oil shale ash, so that the two are fully in contact, creating favorable conditions for the subsequent melt activation reaction.

[0035] 3. Melt activation operation: carefully put the mixed sample into the muffle furnace, set the heating rate of the muffle furnace to 5-10℃ / min, gradually heat it to 500℃, and carry out melt activation reaction at this temperature for 2 hours. During this high temperature process, a series of complex chemical reactions occur inside the sample, which changes the structure and properties of the raw materials. After the melt is cooled to room temperature, grind it again with a mortar and sieve it through a 100-mesh sieve to obtain a melt below 100 mesh. It can be sieved multiple times to ensure the uniformity of the particles.

[0036] 4. Low-temperature aging step: Add an appropriate amount of deionized water to the sieved melt and mix them at a mass ratio of 1:5. Then place the mixed solution in a constant temperature water bath at 25°C and stir and age it at a speed of 200-300r / min for 2 hours under the action of a magnetic stirrer. During this process, the substances in the solution further react under relatively mild conditions to form a more stable and uniform system, laying the foundation for the subsequent crystallization process.

[0037] 5. High-temperature crystallization reaction: The aged product is transferred to a high-pressure reactor and crystallized at a constant temperature of 80°C. The reaction time is set to 12 hours. At this stage, the zeolite crystal structure gradually grows and improves under the action of high temperature and a certain pressure in the reactor, and finally forms a crystallized product. During the crystallization process, it is necessary to ensure that the reactor is well sealed to avoid pressure leakage affecting the crystallization effect.

[0038] 6. Post-processing stage: Use centrifugal separation to separate the crystallized product into solid and liquid. The centrifugal speed is set to 3000-4000r / min and the centrifugal time is 3-10 minutes. The separated solid is repeatedly washed with a large amount of deionized water. The amount of water used for each washing is 5-10 times the mass of the solid, until the pH value of the washing liquid reaches neutrality, ensuring the removal of impurity ions remaining on the surface of the solid. The washed solid is then placed in an oven at 110°C and dried to constant weight. The drying time is about 4-6 hours, and then crushed with a mortar or grinder, and sieved again through a 100-mesh sieve to finally obtain the Barkol oil shale ash-based zeolite adsorption material below 100 mesh.

[0039] 7. Adsorption performance test: The obtained zeolite adsorption material was comprehensively characterized and analyzed using an X-ray diffraction spectrometer (XRD), a scanning electron microscope (SEM) and a nitrogen adsorption-desorption analyzer (BET) to understand its crystal structure, micromorphology and pore structure. Subsequently, the zeolite adsorption material was used to conduct an adsorption experiment on heavy metal cadmium in wastewater. In the experiment, the initial concentration of cadmium ions in the wastewater was set to 200 mg / L, the pH value of the wastewater was adjusted to 7, the adsorption temperature was controlled at 25°C, and the adsorption time was set to 60 minutes. During the adsorption process, the zeolite adsorption material was added to the wastewater and stirred at a speed of 300-400r / min using a magnetic stirrer to allow the material to fully contact the wastewater. After the adsorption was completed, the content of heavy metal cadmium in the wastewater before and after adsorption was measured, and the adsorption amount of cadmium by the zeolite adsorption material was calculated according to the relevant formula. It was tested that the zeolite adsorption material had an excellent treatment effect on wastewater containing heavy metal cadmium.

[0040] Example 2

[0041] 1. Raw material pretreatment: The ash from the combustion of oil shale in Huadian area of ​​Jilin is used as raw material. After drying it at 110°C, it is crushed into a suitable particle size with a pulverizer. The drying time is about 3 hours. The power and time of the pulverizer are controlled during the crushing. Then, it is sieved through a 100-mesh sieve to obtain raw materials below 100 mesh to ensure the consistency and uniformity of the raw materials and meet the requirements of subsequent reactions.

[0042] 2. Alkali mixing and grinding: Mix the obtained raw materials with potassium hydroxide in a mass ratio of 1:1.5, put them into a mortar and grind them evenly. During the grinding process, stir gently for 5-10 minutes to make the two initially mixed, and then grind them for 20-25 minutes with moderate strength and frequency. The grinding time and strength can be appropriately increased to ensure that potassium hydroxide and oil shale ash are fully mixed to promote the smooth progress of subsequent reactions.

[0043] 3. Melt activation and subsequent treatment: Put the mixed sample into a muffle furnace, heat it to 500℃ at a heating rate of 8℃ / min, melt activate it at 500℃ for 2 hours, and grind it through a 100-mesh sieve after cooling. The grinding process can be carried out several times, and sieve it after each grinding to ensure uniform particles. This series of operations ensures that the sample can maintain uniform properties and appropriate particle size after high-temperature treatment, which is conducive to the subsequent steps.

[0044] 4. Aging process: Add appropriate amount of deionized water, mix according to the mass ratio of 1:5, and stir and age for 2 hours at 20°C. During the aging process, stir at a speed of 250r / min. The stirring speed and time can be appropriately optimized to further improve the stability and uniformity of the aged product.

[0045] 5. Crystallization and post-treatment: After the aged product is crystallized at 80°C for 12 hours, a series of post-treatment operations such as centrifugal separation, washing, drying, crushing and screening are performed. The speed of centrifugal separation is 3500r / min, and the centrifugal time is 6 minutes. During washing, it is rinsed with deionized water several times until the washing liquid is neutral. Drying is carried out at 110°C for 5 hours. After crushing, it is passed through a 100-mesh sieve to obtain Huadian oil shale ash-based zeolite adsorption material with a mesh size of less than 100. During the washing process, the number of washing times can be increased to ensure that impurities on the solid surface are completely removed.

[0046] 6. Adsorption experiment: The material was characterized and analyzed. The analysis method and the instrument used were the same as those in Example 1. After the material was characterized and analyzed, it was used to adsorb cadmium. The initial concentration of cadmium ions in the wastewater was set to 250 mg / L, the pH value was 7, the adsorption temperature was 25°C, and the adsorption time was 120 minutes. During the adsorption process, a magnetic stirrer was used to stir at a speed of 350 r / min. Different stirring modes or oscillation frequencies can be tried to observe their effects on the adsorption effect. The adsorption effect is good.

[0047] Example 3

[0048] 1. Raw material processing: Take the ash from the combustion of oil shale in Fushun, Liaoning Province, first dry it at 110°C for 3.5 hours, then crush it and sieve it through a 100-mesh sieve to obtain raw materials that meet the requirements, providing a stable basis for subsequent reactions.

[0049] 2. Mixing and activation: After mixing and grinding with sodium hydroxide at a mass ratio of 1:1.7, put it into a muffle furnace and heat it to 600℃ at a heating rate of 6℃ / min. Melt and activate it at 600℃ for 2 hours, and sieve it after cooling. During the melt activation process, the heating rate and cooling rate of the muffle furnace can be studied and optimized to explore its effect on the performance of the sample.

[0050] 3. Aging and crystallization: Add deionized water at a mass ratio of 1:5, stir and age at 25°C for 2 hours, the stirring speed is 280r / min, and the aged product is crystallized at 80°C for 8 hours. During the aging and crystallization process, the material and shape of the reaction container can be selected and improved to improve the reaction efficiency.

[0051] 4. Post-treatment and adsorption test: After solid-liquid separation, washing, drying, crushing and screening and other post-treatment steps. Solid-liquid separation is carried out by centrifugation, with a centrifugal speed of 3800r / min and a centrifugal time of 10 minutes. After washing to neutrality, it is dried at 110°C for 5.5 hours and crushed through a 100-mesh sieve to obtain Fushun oil shale ash-based zeolite adsorption material below 100 mesh. In the adsorption test, the material is characterized and analyzed. The analysis method and the instruments used are the same as those in Example 1. The initial concentration of cadmium ions in the wastewater is set to 300mg / L, the pH value is 7, the adsorption temperature is 40°C, and the adsorption time is 90 minutes. At the same time, the adsorption performance differences of materials prepared from different batches can be compared, and the adsorption effect is excellent.

[0052] The structural parameters and cadmium adsorption statistics of the zeolite adsorption materials prepared in Examples 1-3 are as follows:

[0053]

[0054] It can be seen from the above examples and statistical tables that the preparation method of the present invention has good stability and repeatability, can prepare oil shale ash-based zeolite adsorption materials with excellent performance, and has significant effects in treating wastewater containing heavy metal cadmium. In the actual operation process, each link can be appropriately optimized and improved according to the specific situation to further improve the performance and preparation efficiency of the material. At the same time, the protection scope of the present invention not only covers the technical solutions described in the above specific embodiments, but also includes equivalent structures or equivalent process changes made using the contents of the present invention specification and drawings, as well as direct or indirect applications in other related technical fields.

[0055] The present invention directly uses solid waste oil shale ash as raw material, does not use acid solution to pretreat the raw material and does not need to add additional silicon-containing or aluminum-containing chemicals, and only uses a simple alkali melting hydrothermal process to prepare a zeolite adsorption material with a clear crystal structure and a smooth surface. The present invention has a simple process for preparing a zeolite adsorption material from oil shale ash, an environmentally friendly process, low cost, and is suitable for large-scale, industrialized production.

[0056] The zeolite adsorption material prepared by the present invention has a large specific surface area and a suitable pore structure, exhibits an excellent adsorption effect on cadmium, and shows a good application prospect.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium, characterized in that: The following steps are involved: S1: Raw material pretreatment: drying, crushing and screening the oil shale ash to obtain raw materials with suitable particle size, wherein the oil shale ash comes from the combustion of oil shale or oil shale semi-coke, and the screening mesh number is between 60-200 mesh; S2: alkali mixing: mixing the pretreated oil shale ash with alkali in a specific ratio and grinding them evenly; S3: Melt activation: The mixed sample is subjected to high temperature melt activation treatment, followed by cooling, grinding and sieving; S4: Aging: Mixing the sieved melt with deionized water in a certain proportion and stirring and aging; S5: performing a constant temperature crystallization reaction on the aged product; S6: Post-treatment: The crystallized product is subjected to solid-liquid separation, washing, drying, crushing and screening to obtain the final zeolite adsorption material.

2. The method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium according to claim 1, characterized in that: In the raw material pretreatment, the drying temperature of the oil shale ash is 80-120°C.

3. The method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium according to claim 1, characterized in that: In the alkali mixing step, the mass ratio of oil shale ash to alkali is controlled at 1:0.5-1:2.5, and the alkali includes sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide and sodium carbonate, and is ground using a mortar or mechanical stirring equipment to ensure uniform mixing.

4. The method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium according to claim 1, characterized in that: In the melt activation step, the melting temperature is 300-900° C., the melting time is 0.5-4 hours, and it is carried out in a muffle furnace or other high-temperature heating equipment. After cooling, it is sieved with a 60-200 mesh sieve.

5. The method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium according to claim 1, characterized in that: In the aging step, the mass ratio of the melt to deionized water is 1:1-1:8, the aging temperature is 10-40° C., and the aging time is 0.5-4 hours.

6. The method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium according to claim 1, characterized in that: In the crystallization step, the crystallization temperature is controlled at 60-120° C., and the crystallization time is controlled at 4-48 hours.

7. The method for preparing an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium according to claim 1, characterized in that: In the post-treatment step, the solid-liquid separation is carried out by centrifugal separation, filtration or static precipitation. The solid is washed to neutrality and then dried at 105-110° C. to constant weight. The sieve used for crushing and screening is 60-200 mesh.

8. An application of an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium, characterized in that: The oil shale ash-based zeolite material for efficiently adsorbing heavy metal cadmium is prepared by the preparation method of the oil shale ash-based zeolite material for efficiently adsorbing heavy metal cadmium as described in any one of claims 1 to 7. The oil shale ash-based zeolite material for efficiently adsorbing heavy metal cadmium is used to adsorb heavy metal cadmium in wastewater. The concentration of cadmium ions in the treated wastewater is 50-600 mg / L, the pH value of the wastewater is 3-9, the adsorption temperature is 10-60°C, and the adsorption time is 1-240 minutes.

9. The use of an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium as claimed in claim 8, characterized in that: During the adsorption process, stirring or shaking is used to ensure that the zeolite adsorption material is fully in contact with the wastewater.

10. The use of an oil shale ash-based zeolite material for efficient adsorption of heavy metal cadmium as claimed in claim 8, characterized in that: The wastewater needs to be initially filtered before adsorption to remove large particle impurities.

Citation Information

Patent Citations

  • Method for preparing zeolite molecular sieve by using oil shale residues

    CN101723397A

  • Method for synthesizing X-type zeolite by modifying oil shale slag

    CN110357122B

  • Method for synthesizing activated carbon analcime from oil shale waste

    CN119100384A